Toward the Total Synthesis of Divergolides C and D - Hager, Anastasia; Kuttruff, Christian A.; Hager, Dominik; Terwilliger, Daniel W.; Trauner, Dirk (Synlett, 2013)
The divergolides are a family of structurally unprecedented ansa macrocycles. We describe a synthetic strategy toward divergolides C and D that hinges on the biomimetic diversification of a common intermediate. An advanced precursor that incorporates all the carbon atoms of divergolide C and D is presented, and atropisomerism in a sterically crowded acyl naphthalene is studied.
Keywords: natural products; ansamycins; macrolides; divergent synthesis; atropisomerism